A REFLECTION ON THE PROBLEMS OF EVALUATING THE COEXISTENCE BALANCE BETWEEN SHORT AND LONG CHAIN IN THE AGRI-FOOD MARKET: SOME IMPACT INDICATORS - Sini, M. Paola (European Scientific Journal, ESJ, 2015)
The contribution made by this article is fundamentally to stimulate international debate on a subject that is not discussed sufficiently, or at least not in the terms indicated here, namely not the debate on the short or long chain efficiency and on the relative convenience of each, but the debate on how to establish research to identify what, in different contexts and globally, may be an excellent balance between short and long chain. How they can best divide the market shares up between them, considering the fact that all possible changes to this “balance of coexistence” on a sub-system level of the local market has an effect some distance away on the global system of markets. This research highlights the complex problems of assessing the optimal coexistence balance (in social wellbeing terms) of long chain and short chain in the food product market on a local and global territorial scale; the evaluation route of a hypothesised procedure to assess this coexistence ratio; the need of constructing suitable food market simulation models designed specifically to identify the above mentioned optimal coexistence balance; the difficulties of constructing these models and the present state of art on market simulation models; the analysis of the environmental, economic, and social impacts of short chain versus long chain in there many facets and related indicators and subindicators to evaluate them within simulation models; the interpretative capacity of these tangible and intagible indicators and the various modes (quantitative, proxy, qualitative data) through which they can measure/assess impacts.